Genetic Regulation of Alginate Production in Azotobacter vinelandii a Bacterium of Biotechnological Interest: A Mini-Review - Núñez, Cinthia; López-Pliego, Liliana; Ahumada-Manuel, Carlos Leonel; Castañeda, Miguel (Frontiers in Microbiology, 2022)
Alginates are a family of polymers composed of guluronate and mannuronate monomers joined by β (1-4) links. The different types of alginates have variations in their monomer content and molecular weight, which determine the rheological properties and their applications. In industry, alginates are commonly used as additives capable of viscosifying, stabilizing, emulsifying, and gelling aqueous solutions. Recently, additional specialized biomedical uses have been reported for this polymer. Currently, the production of alginates is based on the harvesting of seaweeds, however the composition and structure of the extracts are highly variable. The production of alginates for specialized applications requires a precise composition of monomers and molecular weight, which could be achieved using bacterial production systems such as those based on Azotobacter vinelandii, a free-linving, non-pathogenic bacterium. In this mini-review, we analyze the latest advances in the regulation of alginate synthesis in this model.